A Műegyetem az I. világháborúban - Batalka, Krisztina (Gerundium, 2016)
The Royal Joseph Technical University in the First World War. The First World War gave new challenges to the Royal Joseph Technical University: in its functioning (e.g. maintaining a military hospital), in teaching and researching (student soldiers, military-related innovation) and in social activities (livelihood in the hinterland) as well. In addition some important education issues culminated in those years: the reform of the technical education system (simultaneously with the formation of the department of economy),and the establishment of the second and third Hungarian technical university. However, the emancipation of women may be considered one of the achievements of World War I, it only partially prevailed at the university. Nevertheless the socio-economic role of the university, including the importance of more-specialized and practical knowledge transfer, was highly appreciated during the war. The publication provides a brief summary of the subject based on those unused sources which can be found in the university's archives.